The effect of Si addition and thermomechanical processing in an Fe-Mn alloy for biodegradable implants: Mechanical performance and degradation behavior. (June 2021) - Fiocchi, J.; Lemke, J.N.; Zilio, S.; Biffi, C.A.; Coda, A.; Tuissi, A.
Graphical abstract: Highlights: Microstructure is refined and homogeneity preserved by adding Si to Fe-Mn. Austenite to Martensite ratio can be fine-tuned by thermomechanical processing. Si lowers the alloy's stacking fault energy granting combined strength and ductility. Si slows initial corrosion down, but increases degradation rate in the long term. Abstract: Among iron-based materials, the Fe-Mn system appears to be highly suitable for the development of biodegradable metals for orthopaedic and vascular applications. The versatility of tailoring such steels by alloying provides many opportunities to customise biodegradable devices. In the field of applications where a high load-bearing capacity is required, the addition of Si could constitute an effective strategy to improve the mechanical properties while maintaining a similar corrosion susceptibility and biocompatibility. In this study, the microstructure, mechanical properties, and corrosion behaviour of Fe-30 Mn-5Si (wt.%) alloy are presented, discussed, and assessed in comparison with a binary Fe-30 Mn formulation. Emphasis is placed on characterising the alloys in processed conditions by using conventional thermomechanical rolling and annealing techniques, which are feasible and allow for scale-up. Such techniques affect phases equilibrium, internal stresses and grain size, thus altering the degradation behaviour. The addition of Si resulted in excellent microstructural homogeneity and was used to tailor the relative abundances of austenitic and martensitic phases by applying different heat treatment strategies. As a result, the mechanical resistance was improved by 70 % compared to the base alloy, the strain hardening ability was improved while keeping good ductility. Electrochemical corrosion tests and static degradation experiments showed that both alloys corrode at a similar rate, although the addition of Si appeared to induce a slower degradation in the initial stage and a faster one in the long term.